Penegakan Hukum Kejahatan Perang Berdasarkan Kewenangan Mahkamah Pidana Internasional - Muklis Al'anam; Hotland Thomas (Jurnal Hukum Lex Generalis, 2024)
War crimes in the Charter of the International Military Tribunal 1945 and listed in the Treaty of London 8 August 1945. War crimes are extraordinary crimes as gross violations of human rights. Therefore, in 1998 in Rome, 120 UN member states enacted the statute establishing the International Criminal Court (ICC). The ICC aims to provide human rights protection to victims and law enforcement of war crimes perpetrators. This article aims to examine the important role of the ICC in the enforcement of war crimes in the aspect of contemporary criminal law, based on the nortmative legal research method. The results show the important role of human rights enforcement in the criminal law aspect of war crimes.